Use of Nickel Slag As An Aggregate Replacement Material In Weared Asphalt Concrete Mixtures - Bethary, Rindu Twidi; Intari, Dwi Esti; Pradana, Muhammad Fakhruriza; Al Hadiana, Muhamad Fadhil (JURUSAN TEKNIK SIPIL, 2024)
The increase in development growth throughout the world every year is directly proportional to the increase in demand for construction materials. To overcome the very limited sources of natural materials, alternative materials are needed as substitutes for construction materials. Utilizing nickel slag waste as an alternative material to replace natural aggregate in order to reduce the extraction of excess natural aggregate and preserve limited natural resources. The purpose of this study was to determine the Marshall characteristics and ideal composition for using nickel slag as a substitute for aggregate in worncoated asphalt concrete (AC-WC) mixtures. The test specimens used were a mixture of worn coated asphalt concrete (AC-WC) with variations in nickel slag content, namely 0%, 10%, 40% and 70% and optimum asphalt content (KAO) respectively of 5.5%; 6%; 5.5%; and 5%. Based on the results of study that has been carried out, the optimum stability value was obtained at 1087.38 kg at a nickel slag content of 70% with an optimum asphalt content (KAO) of 5%. This value is greater than the stability value obtained at a nickel slag content of 0% with an asphalt content. optimum 5.5%, namely 1034.39 kg. From these results it can be concluded that nickel slag can improve the performance of worn coated asphalt concrete (AC-WC) mixtures and the ideal composition of nickel slag is at a nickel slag content of 70% with an optimum asphalt content (KAO) of 5%.